Vitamin D3 Deficiency’s Impact on Atrial Fibrillation in Hyperthyroidism Patients - Hanash Dhefer , Iqbal (Diyala Journal of Medicine, 2024)
Background: Atrial fibrillation (AFi) is more common as people get older. Additionally, a further indicator of the occurrence of AFi is subclinical hyperthyroidism, which is linked to a 3-fold increased risk. Lack of vitamin D causes the renin-angiotensin-aldosterone pathway to become active, which has an impact on the cardiovascular system. Objective: To examine the association between 25-hydroxyvitamin D3 insufficiency and AFi and hyperthyroidism cases with valvular and nonvalvular AFi that required treatment at our medical center. Patients and Methods: Samples taken from 200 cases of AFi (50-65 years old) divided into: group A cases with nonvalvular AFi and group B cases with valve AFi, and 100 healthy individuals with sinus rhythm who were age-matched chosen as control groups. Standard biochemical measurements, including levels of 25-OHvit.D3,the hormone of the thyroid gland, and parathyroid hormone, were made. Results: Cases in group A had decreased 25-OHvit.D3 levels compare to those in the control and B groups (P ≤ 0.05 ).In comparison to the control group, the patients in groups A and B had larger left atriums and greater systolic pulmonary artery pressures. Conclusion: Thus, the study shows a connection between nonvalvular AFi cases with hyperthyroidism and 25-OHvit D3 deficiency.